COMPARATIVE ANALYSIS OF OPC BRANDS COMMONLY USED IN KURDISTAN REGION-IRAQ - SELMAN, MUDHAFER H. (Journal of Duhok University, 2021)
Nowadays the brand of cement used in construction works is selected mostly on experience, availability, and cost. This study aims to evaluate and compare the chemical and physical properties of five brands of commercial ordinary Portland cement (OPC) available in the Kurdistan region, which are (Mass, Delta, Kar, Mardin, and Şanliurfa). Several tests on each cement brand’s sample have been done in the laboratory to analyze their properties according to British Standards (BS). The chemical composition of the cement brands was analyzed by x-ray fluorescence method and the cement tests also include (normal consistency, initial setting time, final setting time, soundness, loss of ignition, fineness, flexural strength, and compressive strength). The effect of chemical composition on the mechanical properties also studied. The results show that all samples have chemical contents within the acceptable limits. Şanliurfa cement has the highest compressive strength at 28 days with 55.4 N/mm2and it is about 27.7% more than Kar cement, which has the lowest compressive strength of all tested cement brands. The MgO/SO3 ratio results show that the Şanliurfa cement has the lowest ratio with 0.62 comparing with other cement brandsand this influences its compressive strength results. The (Mardin, Mass, Delta, and Kar) cement were found to be classified as 42.5N class, these cement brands recommended to be used in bearing concrete structural elements, commercial ready mix concrete plants, and rigid pavement construction work. On the other hand, the study found that Şanliurfa cement classified as 52.5N class and it is recommended to use in high strength concrete works.